Kinetics of skin resealing after insertion of microneedles in human subjects - Gupta, Jyoti; Gill, Harvinder S.; Andrews, Samantha N.; Prausnitz, Mark R. (Journal of controlled release, 2011)
Over the past decade, microneedles have been shown to dramatically increase skin permeability to a broad range of compounds by creating reversible microchannels in the skin. However, in order to achieve sustained transdermal drug delivery, the extent and duration of skin's increased permeability needs to be determined. In this study, we used electrical impedance spectroscopy to perform the first experiments in human subjects to analyze the resealing of skin's barrier properties after insertion of microneedles. Microneedles having a range of geometries were studied in conjunction with the effect of occlusion to test the hypothesis that increasing microneedle length, number, and cross-sectional area together with occlusion leads to an increase in skin resealing time that can exceed one day. Results indicated that in the absence of occlusion, all microneedle treated sites recovered barrier properties within 2 h, while occluded sites resealed more slowly, with resealing windows ranging from 3 to 40 h depending on microneedle geometry. Upon subsequent removal of occlusion, the skin barrier resealed rapidly. Longer microneedles, increased number of needles, and larger cross-sectional area demonstrated slower resealing kinetics indicating that microneedle geometry played a significant role in the barrier resealing process. Overall, this study showed that pre-treatment of skin with microneedles before applying an occlusive transdermal patch can increase skin permeability for more than one day, but nonetheless allow skin to reseal rapidly after patch removal. Skin pre-treatment with microneedles can increase skin permeability for more than one day, but nonetheless allow skin to reseal rapidly after patch removal. [Display omitted]